PENGARUH LIKUIDITAS, JANGKA WAKTU JATUH TEMPO, DAN KUPON OBLIGASI TERHADAP HARGA OBLIGASI PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017-2019 - I Dewa Ayu Sri Ratna Purwani; I Wayan Sukadana; I Wayan Suarjana (VALUES, 2022)
This study aims to determine the effect of liquidity, maturity period and bond coupons on the price of company bonds listed on the Indonesia Stock Exchange. This research was conducted on companies that issued bonds on the Indonesia Stock Exchange in the period 2017 to 2019. The number of samples used in this study was 93 bonds. Based on the results of the analysis, it was found that liquidity had no effect on changes in bond prices for the 2017-2019 period. The maturity period has a negative effect on changes in bond prices for the 2017-2019 period. Coupons have a positive and significant effect on changes in bond prices for the 2017-2019 period.